The effect of long-term service exposure on the stability of carbides in Co–Cr–Ni–W (X-45) superalloy. (February 2018) - Zangeneh, Sh.; Lashgari, H.R.; Asnavandi, M.
Abstract: The present study was conducted to investigate the effect of long-term thermal exposure during service on the microstructure and tensile properties of Co–Cr–W alloy (known as X-45 alloy) used as the first stage nozzle in a gas turbine engine. Samples for the microstructure and tensile properties were cut from the side wall and trailing edge exposed to 700 °C and 800 °C, respectively, for various durations, i.e. 12, 000 h, 16, 000 h, and 18, 000 h. At temperature around 800 °C, the irregular coarse M23 C6 carbides precipitate at the grain boundaries and interior of the grains from the decomposition of M6 C → M23 C6 whereas M23 C6 carbides precipitation occurs directly on the stacking faults and grain boundaries at 700 °C due to the reaction of 23 M + 6C → M23 C6 . The tensile results indicate the correlation of the exposure time to morphology and dispersion of carbides. Small and shallow dimples were the main fracture mode of the exposed samples to 800 °C while intergranular fracture mode was observed in the samples exposed to 700 °C. Highlights: The effect of long-term high temperature service exposure in Co-Cr-Ni-W alloy Precipitation of M23 C6 carbides directly on stacking faults due to exposure at 700 °C for lengthy time (23 M + 6C → M23 C6 ) Precipitation of the irregular coarse M23 C6 carbides at grain boundaries and/or interior of grains due to exposure at 800 °C (M6 C → M23 C6 ) Observation of small and shallow dimples in samples exposed at 800 °C for lengthy time Intergranular fracture mode due to the continuous secondary carbides film at grain boundaries